Capiteles tardíos del sur del Conventus Carthaginiensis (ss. IV-VII d.C.) - Martínez Rodríguez, Andrés (Antigüedad y Cristianismo, 1998)
The author having studied earlier capitals from "altiplano" (region of Yecla and Jumilla) and those of the Archaeological Museum of Murcia here offers a group of eleven capitals from the south of the Conventus Carthaginiensis al1 belonging to the centuries of late antiquity (III-VIII). After a description and some indications about their geographical locations the author studies the typology by which they could be classified: Corinthian and other Corinthian styles and the typology of those which are difficult to group. He finishes with some reflections on the art of this type of work and the sociocnltural conditions in which they were produced. (...)